(Neo)liberalne uwikłania emancypacyjnego paradygmatu pedagogiki specjalnej - Wlazło, Marcin (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2015)
Education and rehabilitation of people with disabilities are included in the mainstream of social life as a realization of a particular model accounting for both human beings and human relationships. The emplacement of disability and the tasks of special edu-cation in the emancipatory paradigm implies acceptance of the principles derived from the assumptions of liberalism as a concept explaining the essence of human freedom. At the same time the emancipatory trend in the sciences of education has clearly socio-political nature, which essence is the opposition to ideological and economic domina-tion and exclusion of certain social groups. To a large extent it is the opposition to the rules of the neoliberal economy, treated as a source of social and economic crisis. This article presents the relationship between the idea of freedom and the free market in the context of the social model of disability and special education emancipatory paradigm.